Scandal, Protection, and Recovery in Political Cabinets. - Dewan, T; Myatt, D (Department of Economics (University of Oxford), 2005)
Empirical evidence suggests that a Prime Minister can benefit from firing ministers who are involved in political scandals. We explore a model in which a minister's exposure to scandals is positvely related to his policy activism, so that a Prime Minister may wish to protect him from resignation calls. We find that protection can sometimes work against the objective of encouraging activism: it makes a minister's position more valuable to him and hence can encourage him to "sit tight" by moderating his activities. On the other hand, an exogenous increase in exposure to scandals may lead a minister to "live for today" by pursuing controversial policy innovations. The Prime Minister's ability to protect ministers from resignation calls is limited by her short-term incentive to fire. She may, however, enhance her credibility by building a collective reputation with the wider membership of her cabinet; we show that heterogeneity of cabinet membership can play an important role.